The origins of cognitive dissonance evidence from children and monkey - Egan, Louisa G.; Santos,Laurie R.; Bloom, Paul (Sage Publications, 2007)
In a study exploring the origins of cognitive dissonance, preschoolers and capuchins were given a choice between two equally preferred alternatives (two different stickers and two differently colored M&M's, respectively). On the basis of previous research with adults, this choice was thought to cause dissonance because it conflicted with subjects' belief that the two options were equally valuable. We therefore expected subjects to change their attitude toward the unchosen alternative, deeming it less valuable. We then presented subjects with a choice between the unchosen option and an option that was originally as attractive as both options in the first choice. Both groups preferred the novel over the unchosen option in this experimental condition, but not in a control condition in which they did not take part in the first decision. These results provide the first evidence of decision rationalization in children and nonhuman primates. They suggest that the mechanisms underlying cognitive-dissonance reduction in human adults may have originated both developmentally and evolutionarily earlier than previously thought.